Penentuan Kelayakan Pembiayaan Pada Koperasi Syari'ah Mitra Insan Mandiri Menggunakan Metode Simple Additive Weighting; - Yusuf Sumaryana; Gea Aristi (Jurnal ICT: Information Communication & Technology, 2021)
The assessment of the feasibility of financing carried out by the Cooperative for Savings and Loans and Syari'ah Partners Insan Mandiri is still using the manual method, which is carried out by cooperative officers. In this case, there needs to be an effort to improve services in providing financing, so a decision support system is made to determine the feasibility of using the Simple Additive Weighting Method. The scoring system is carried out using the 5C Criteria, namely Character, Capacity, Capital, Collateral, Condition of Economy. This decision support system results in a more precise and accurate creditworthiness assessment. The results can certainly minimize the risk of bad credit or other problems that can harm the Savings and Loans Cooperative and Syari'ah Mitra Insan Mandiri financing. The process of determining the feasibility of this financing goes through 5 (five) stages, namely (1) Determining criteria and alternatives, (2) Determining the weight of each criterion, (3) Creating a matrix of each criterion, (4) Normalizing the Matrix, (5) Ranking the results alternative recommendations.